Identification of a novel germline BRCA2 variant in a Chinese breast cancer family. Issue 2 (28th November 2019) - Cheng, Jingliang; Peng, Jiangzhou; Fu, Jiewen; Khan, Md. Asaduzzaman; Tan, Pingping; Wei, Chunli; Deng, Xiyun; Chen, Hanchun; Fu, Junjiang
Abstract: Breast cancer is the most frequently diagnosed cancer and the leading cause of cancer‐related deaths in women worldwide. In this study, a large Chinese pedigree with breast cancer including a proband and two female patients was recruited and a familial history of breast cancer was collected by questionnaire. Clinicopathological assessments and neoadjuvant therapy‐related information were obtained for the proband. Blood samples were taken, and gDNA was extracted. The BRCA1/2 and PALB2 genes were screened using next‐generation sequencing by a targeted gene panel. We have successfully identified a novel, germline heterozygous, missense mutation of the gene BRCA2 : c.7007G>T, p.R2336L, which is likely to be pathogenic in the proband and her elder sister who both had breast cancer. Furthermore, the risk factors for developing breast cancer in this family are discussed. Thus, genetic counselling and long‐term follow‐up should be provided for this family of breast cancer patients as well as carriers carrying a germline variant of BRCA2 : c.7007G>T (p.R2336L).